Endothelial dysfunction, thrombophilia, and nailfold capillaroscopic features in livedoid vasculopathy - ALİBAZ ÖNER, FATMA (My University, 2023)
Background: Livedoid vasculopathy (LV) is a rare, disabling disease characterized by painful ulcers, livedo reticularis and atrophy blanche. Hypercoagulation, endothelial, and microcirculatory dysfunction are believed to be responsible for the pathogenesis of this difficult-to-treat disease. Objectives: This study sought to investigate the frequency of endothelial dysfunction, hypercoagulability, and nailfold capillaroscopic features in LV patients to shed light on its etiology. Methods: This case-control study included 16 patients with LV, 24 with systemic sclerosis (SSc), and 23 control subjects. Serum markers of endothelial dysfunction soluble endoglin, endocan, endothelin-1, lipoprotein a, plasminogen activator inhibitor-1 (PAI-1), soluble thrombomodulin, and von Willebrand factor were measured using enzyme-linked immunosorbent assays. Flow-mediated dilation and carotid intima-media thickness were examined as markers of endothelial dysfunction, and microcirculation was assessed with nailfold capillaroscopy. Thrombophilia-related parameters, including gene polymorphisms of factor V Leiden, prothrombin, PAI-1 genes, methylenetetrahydrofolate reductase (MTHFR) and factor XIII mutation and serum levels of protein C, protein S, antithrombin, homocysteine, D-dimer and antiphospholipid antibodies were investigated in LV patients. Results: Plasminogen activator inhibitor-1 and soluble thrombomodulin levels were significantly higher in LV patients compared to control subjects (2.3 [2.05–2.79] ng/ml vs. 1.89 [1.43–2.33] ng/ml, p = 0.007; 1.15 [0.88–1.4] ng/ml vs. 0.76 [0.56–0.9] ng/ml, p = 0.004, respectively). Flow-mediated dilation was 25.4 % lower in the LV patients compared to the control group (14.77 % [11.26–18.26] vs. 19.80 % [16.47–24.88], p = 0.034). Capillaroscopic features, including ramifications (75 % vs. 8.7 %, p < 0.001), avascular areas (25 % vs. 0 %, p = 0.011) and dilatations (33.2 % vs. 0 %, p = 0.016), were significantly higher in LV patients than in controls. LV patients had multiple biochemical or genetic abnormalities related to thrombophilia, including heterozygous factor V Leiden mutations (6.3 %), MTHFR (C677T) mutations (heterozygous 43.8 %, homozygous 18.8 %), MTHFR (A1298C) mutations (heterozygous 37.5 %, homozygous 12.5 %), factor XIII heterozygous mutation (12.5 %), antithrombin deficiency (31.3 %), protein S deficiency (12.5 %), hyperhomocysteinemia (31.3 %), Ddimer elevation (25 %), anti-β2-glycoprotein I (12.5 %), lupus anticoagulant antibodies (6.3 %), and anticardiolipin antibodies (6.3 %). Conclusions: In conclusion, LV patients were characterized by an increased presence of thrombophilia-related parameters, and also exhibited vascular endothelial and microcirculatory dysfunction, resembling SSc. These findings support the complex interaction of thrombophilia, endothelial dysfunction, and microcirculation dysregulation in the pathogenesis of LV. Thus, the treatment of LV patients should be individualized, based on the identification of the predominant pathological pathways.
Keywords: Capillaroscopy; Coagulopathy; Endothelial dysfunction; Livedo; Livedoid vasculopathy; Microcirculation